Optimization of a grid of candidates in the search procedure of the MAFA method - Cellmer, Slawomir; Nowel, Krzysztof; Kwasniak, Dawid (International Conference “Environmental Engineering”, 2017)
Precise, carrier phase-based positioning requires a search procedure for “fixed solution” i.e. a solution, that takes into account the integer nature of ambiguities. In the classical approach (the Lambda method) the search for a fixed solution is conducted in the ambiguity domain. The computational load in this case depends on a number of satellites (the dimension of an ambiguity space amounts to: the number of satellites minus one). Conversely, in the MAFA method the search procedure is conducted in the coordinate-domain, (i.e. in three-dimensional space). It considerably reduces the computational load. In the article the search procedure in the coordinate domain is described. The technique of forming the optimized grid of candidates is presented, and the results of the tests are presented and analyzed.
Keywords: mixed integer-real least squares; GNSS data processing; Voronoi cell